Physicians’ Workload and Quality Healthcare in Indonesia - Rovy Pratama; Amanda Yufika (School of Medicine, Universitas Syiah Kuala, 2023)
Indonesian law regulates that physicians might work in maximum three places. This policy results in increased workload, which might lead to burnout, affecting the quality care. This review aimed to explore how physicians’ workload affect the quality healthcare in Indonesia. We found that most Indonesian physicians worked long hours due to the current policy allowing them to work in maximum three medical centers. Vast majority of doctors in Indonesia also had to deal with abundant administrative works, especially since the implementation of Jaminan Kesehatan Nasional (JKN). Excessive workload increased work-related stress and job dissatisfaction, which eventually increased physician’s burnout. All these results in poorer quality healthcare. One of the solutions is to regulate physicians to only work at one healthcare facility (Mono-loyalty). However, a careful consideration and thorough preparation to adopt this policy is warrant.